Practice and challenges for organ donation after medical assistance in dying: A scoping review including the results of the first international roundtable in 2021. Issue 12 (26th October 2022) - Mulder, Johannes; Sonneveld, Hans; Van Raemdonck, Dirk; Downar, James; Wiebe, Kim; Domínguez‐Gil, Beatriz; Healey, Andrew; Desschans, Bruno; Neyrinck, Arne; Blanco, Alicia Pérez; van Dusseldorp, Ingeborg; Olthuis, Gert
Abstract : The procedure combining medical assistance in dying (MAiD) with donations after circulatory determination of death (DCDD) is known as organ donation after euthanasia (ODE). The first international roundtable on ODE was held during the 2021 WONCA family medicine conference as part of a scoping review. It aimed to document practice and related issues to advise patients, professionals, and policymakers, aiding the development of responsible guidelines and helping to navigate the issues. This was achieved through literature searches and national and international stakeholder meetings. Up to 2021, ODE was performed 286 times in Canada, the Netherlands, Spain, and Belgium, including eight cases of ODE from home (ODEH). MAiD was provided 17, 217 times (2020) in the eight countries where ODE is permitted. As of 2021, 837 patients (up to 14% of recipients of DCDD donors) had received organs from ODE. ODE raises some important ethical concerns involving patient autonomy, the link between the request for MAiD and the request to donate organs and the increased burden placed on seriously ill MAiD patients. Abstract : This comprehensive overview of organ donation after medical assistance in dying and its attendant issues reports an increasing frequency of this practice internationally.